The effect of materials architecture in TiO2/MOF composites on CO2 photoreduction and charge transfer - Crake,A; Christoforidis,K; Gregg,A; Moss,B; Kafizas,A; Petit,C (Small, 2019)
CO2 photoreduction to C1/C1+ energized molecules is a key reaction of solar fuel technologies. Building heterojunctions can enhance photocatalysts performance, by facilitating charge transfer between two heterojunction phases. The material parameters that control this charge transfer remain unclear. Here, it is hypothesized that governing factors for CO2 photoreduction in gas phase are: i) a large porosity to accumulate CO2 molecules close to catalytic sites and ii) a high number of “points of contact” between the heterojunction components to enhance charge transfer. The former requirement can be met by using porous materials; the latter requirement by controlling the morphology of the heterojunction components. Hence, composites of titanium oxide or titanate and metal–organic framework (MOF), a highly porous material, are built. TiO2 or titanate nanofibers are synthesized and MOF particles are grown on the fibers. All composites produce CO under UV–vis light, using H2 as reducing agent. They are more active than their component materials, e.g., ≈9 times more active than titanate. The controlled composites morphology is confirmed and transient absorption spectroscopy highlights charge transfer between the composite components. It is demonstrated that electrons transfer from TiO2 into the MOF, and holes from the MOF into TiO2, as the MOF induces band bending in TiO2.